1994
DOI: 10.1063/1.356123
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of growth of YBa2Cu3O7−δ high T c superconducting films on (001) Y-ZrO2 substrates

Abstract: The early stages of growth of high quality YBa2Cu3O7−δ (YBCO) films grown on (001) Y-ZrO2 (YSZ) substrates by pulsed laser deposition have been studied using a combination of atomic force microscopy and transmission electron microscopy. A one unit cell thick YBCO layer and relatively large CuO particles formed in the initial stages. Additional YBCO grew on top of the first layer in the form of one or a few unit cell high c-axis oriented islands about 30 nm in diameter. The rounded islands subsequently coalesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…The observations of one unit cell high steps of the YBCO interface are in accord with previous observations by TEM and atomic force microscopy (AFM) of c-axis oriented YBCO films on a wide variety of substrates (e.g., [26][27][28][29][30][31]). The interface smoothness is an important issue for multilayer structures since the surface roughness will put an intrinsic limit to the minimum thickness which is necessary for separation between individual layers A two-dimensional growth mechanism is desirable.…”
Section: Interface Morphologysupporting
confidence: 79%
“…The observations of one unit cell high steps of the YBCO interface are in accord with previous observations by TEM and atomic force microscopy (AFM) of c-axis oriented YBCO films on a wide variety of substrates (e.g., [26][27][28][29][30][31]). The interface smoothness is an important issue for multilayer structures since the surface roughness will put an intrinsic limit to the minimum thickness which is necessary for separation between individual layers A two-dimensional growth mechanism is desirable.…”
Section: Interface Morphologysupporting
confidence: 79%
“…7,8,11 However, no experimental evidence for such a mechanism has been reported, and our investigation of this phenomenon supports an alternative explanation, which is described below. 19,34 In this paper we show that if the growth conditions are such that a BaZrO 3 epitaxialreaction layer forms before the nucleation of the overlying YBa 2 Cu 3 O 72d layer, ϳ9 ± in-plane rotations of the overlying YBa 2 Cu 3 O 72d layer are favored. 19,34 In this paper we show that if the growth conditions are such that a BaZrO 3 epitaxialreaction layer forms before the nucleation of the overlying YBa 2 Cu 3 O 72d layer, ϳ9 ± in-plane rotations of the overlying YBa 2 Cu 3 O 72d layer are favored.…”
Section: Introductionmentioning
confidence: 72%
“…In the former unconstrained case, the BaZrO 3 is oriented (as we demonstrate below) with ͑110͒ BaZrO3 k ͑001͒ YSZ and ͓111͔ BaZrO3 k ͓110͔ YSZ , whereas in the latter constrained case the BaZrO 3 is oriented with ͑001͒ BaZrO3 k ͑001͒ YSZ and ͓100͔ BaZrO3 k ͓100͔ YSZ , 8,19,33,34 or ͑001͒ BaZrO 3 k ͑001͒ YSZ and ͓110͔ BaZrO3 k ͓100͔ YSZ , 8,14 or ͑110͒ BaZrO3 k ͑001͒ YSZ and ͓001͔ BaZrO 3 k ͓100͔ YSZ . In the former unconstrained case, the BaZrO 3 is oriented (as we demonstrate below) with ͑110͒ BaZrO3 k ͑001͒ YSZ and ͓111͔ BaZrO3 k ͓110͔ YSZ , whereas in the latter constrained case the BaZrO 3 is oriented with ͑001͒ BaZrO3 k ͑001͒ YSZ and ͓100͔ BaZrO3 k ͓100͔ YSZ , 8,19,33,34 or ͑001͒ BaZrO 3 k ͑001͒ YSZ and ͓110͔ BaZrO3 k ͓100͔ YSZ , 8,14 or ͑110͒ BaZrO3 k ͑001͒ YSZ and ͓001͔ BaZrO 3 k ͓100͔ YSZ .…”
Section: Introductionmentioning
confidence: 84%
“…For example, the authors of [9] reported that phase Y 2 BaCuO 5 (211) particles having a characteristic pro late shape form on YSZ substrates at the early stages of YBCO growth. However, careful XRD analysis did not reveal other phases apart from the YBa 2 Cu 3 O 7 -δ (123) phase in the films under study.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, the chemical interaction between a film and the substrate is possible at the characteristic YBCO epitaxy temperatures. The authors of [8,9] detected the formation of a textured transition BaZrO 3 layer between YBCO and YSZ, which is caused by the diffusion of Ba from the film to the substrate.…”
Section: Introductionmentioning
confidence: 98%